Law Enforcement Against Indonesian National Army Soldiers Who Committed the Crime of Desertion in Military Trials - Raprap, Stany; Titahelu, Juanrico Alfaromona Sumarezs; Supusepa, Reimon (PAMALI: Pattimura Magister Law Review, 2026)
Introduction: Military crimes are actions committed by the legal subject, namely the military and are called pure military crimes (zuiver militaire delict), where the criminal act is only committed by a military person, because it is special to the military. Criminal acts committed by soldiers of the Indonesian National Army are purely military based on regulations related to the military. One of the criminal acts that is categorized as pure criminal acts is desertion. As stipulated in Article 87 paragraph (1) of the Military Criminal Code. An Indonesian National Army soldier can be sentenced to discipline, imprisonment and dismissal from service.Purposes of the Research: This study aims to find out the law enforcement process for TNI soldiers who commit the crime of desersi, and the legal consequences if an Indonesian National Army soldier who is examined in absentia in a case of criminal displacement.Methods of the Research: This study uses a normative juridical research method, which aims to determine the law enforcement process against Indonesian National Army soldiers who commit desertion crimes, and the legal consequences if an Indonesian National Army soldier who is examined in absentia in a desertion crime case.Results Main Findings of the Research: The Indonesian National Army who commit the crime of desertion cannot be resolved through military disciplinary law but must be resolved through a court hearing. Therefore, the one who has the right to prosecute the crime of desertion is the Military Judge in the Military Criminal Justice System guided by the Military Criminal Code and laws and regulations related to military justice and its sanctions, the second is the legal consequence if an Indonesian National Army soldier who is examined in absentia in a case of desertion cannot file a defense and cannot present evidence as it should, so the Panel of Judges agrees and agrees with the Military Inspectors to examine and decide this case in absentia.